Prostaglandin E2 As a Modulator of Viral Infections - Sander, Willem J.; O'Neill, Hester G.; Pohl, Carolina H. (Frontiers in Physiology, 2017)
Viral infections are a major cause of infectious diseases worldwide. Inflammation and the immune system are the major host defenses against these viral infection. Prostaglandin E2 (PGE2), an eicosanoid generated by cyclooxygenases, has been shown to modulate inflammation and the immune system by regulating the expression/concentration of cytokines. The effect of PGE2 on viral infection and replication is cell type- and virus-family-dependent. The host immune system can be modulated by PGE2, with regards to immunosuppression, inhibition of nitrogen oxide (NO) production, inhibition of interferon (IFN) and apoptotic pathways and inhibition of viral receptor expression. Furthermore, PGE2 can play a role in viral infection directly by increasing the production and release of virions, inhibiting viral binding and replication, and/or stimulating viral gene expression. Prostaglandin E2 may also have a regulatory role in the induction of autoimmunity and in signaling via Toll-like receptors. In this review the known effects of PGE2 on the pathogenesis of various infections caused by herpes simplex virus, rotavirus, influenza A virus and human immunodeficiency virus as well the therapeutic potential of PGE2 are discussed.